Transfer of passive immunity in dairy calves: the effectiveness of providing a supplementary colostrum meal in addition to nursing from the dam. (7th May 2019) - Lora, I.; Gottardo, F.; Bonfanti, L.; Stefani, A. L.; Soranzo, E.; Dall'Ava, B.; Capello, K.; Martini, M.; Barberio, A.
Abstract : Failed transfer of passive immunity (FTPI ) in dairy calves – which is often due to the low amount of colostrum provided within a few hours after birth – remains a crucial issue. Enabling dairy calves to nurse colostrum from their dams could be useful in increasing intake and thus avoiding FTPI, but further potential effects on the health and welfare of both calves and dams should also be considered. In this study, 107 calf-dam pairs from two Italian dairy farms were alternately assigned to one of the following colostrum provision methods (CPMs ): 'hand-fed method' (HFM ) – the calf was separated from the dam immediately after birth and colostrum was provided by nipple-bottle (n = 50); 'nursing method' (NM ) – the calf nursed colostrum from the dam for the first 12 h of life without farmer assistance (n = 30); and 'mixed method' (MM ) – the nursing calf received a supplementary colostrum meal by nipple-bottle (n = 27). Serum of calves (1 to 5 days of age) and samples of their first colostrum meal were analysed by electrophoresis to assess immunoglobulin (Ig ) concentration. Additionally, behavioural indicators of separation distress (calf and dam vocalisations; calf refusal of the first meal after separation; undesirable dam behaviour at milking) in the following 24 h were recorded as binary variables (Yes/No), and the health status of calves (disease occurrence and mortality) and dams (postpartum disorders and mastitis occurrence) were monitored for the first 3 months of life and 7 days after parturition, respectively. The lowest FTPI occurrence (calf serum Ig concentration <10.0 g/l) was found in the MM (11.1%) and the HFM (22.0%) compared with the NM (60.0%) (P<0.05), and the highest percentage of calves with optimal transfer of passive immunity (serum Ig concentration ≥16.0 g/l) was observed in the MM (55.6%). The lowest calf–dam separation distress was observed in the HFM (P<0.05). The highest calf disease occurrence was recorded in the HFM (64.0%) and the lowest in the NM (33.3%), with an intermediate value for the MM (44.4%) (P<0.05). No effect of the CPM was observed on dam health or calf mortality (P>0.05). The results of this study indicated that providing calves with a supplementary colostrum meal in addition to nursing from the dam (MM) is truly effective in maximizing passive immunity transfer. Anyway, specific strategies should be studied to minimise calf-dam separation distress.